Discrete-time resilient-distributed secondary control strategy against unbounded attacks in polymorphic microgrid - Wang, Fuzhi; Shan, Qihe; Zhu, Jun; Xiao, Geyang (Frontiers in Energy Research, 2022)
This paper proposes a polymorphic cooperative control system for microgrid consisting of a service layer, a control layer, a data layer and a power layer to apply resilient distributed secondary control strategy to distributed generators (DGs) from different manufacturers more conveniently. Due to the improvement of network openness, external cyberattacks are more likely to tamper with the neighbor information transmitted in the cooperative control system. A discrete-time resilient distributed secondary control strategy is designed to resist potential unbounded false data injection (FDI) attacks in this paper, which introduces a virtual network layer interconnecting the control network layer to form a layered network. The strategy can maintain the stability of voltage and frequency under unbounded attacks, and then suppress the state estimation difference of voltage and frequency greatly. Meanwhile, the unbounded attack depending on voltage and frequency estimation difference is suppressed to a nearly bounded attack. Finally, a microgrid consisting of 6 inverter-based DGs is taken as an example to validate the effectiveness of the strategy against unbounded attacks.